Result of Combined Mifepriston and Misoprostol in Termination of Early Pregnancy at Different Gestational Age - Roy, Marlina; Khan, Rokeya; Hasan, Nasrin; Karim, Rehnuma; Nasrin, Alifa; Rahman, Nahida (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: An estimated 56 million induced abortion occured each year worldwide. Indirect estimates suggest more than 1.2 million annual menstrual regulations (MRs) and induce abortions each year in Bangladesh. Maternal mortality in Bangladesh is 1.76 /1000 live birth, one fourth of these deaths are due to complication of induced abortion. The safety of procedure is therefore of global public health importance. Now medical abortion option have made more available to women in a variety of health care setting and home administration of medical abortion is acceptable. Objective: To know the outcome and safe use of mifepristone and misoprostol combination up to 9 weeks (<63 days) of missed period to reduce the maternal morbidity, mortality related to complications of menstrual regulation (MR) and induced abortion in Bangladesh. Materials and Methods: This was a prospective cross sectional study of outdoor patients (100 cases) of Marie Stopes Premium Maternity Hospital, Mirpur-10 who came for menstrual regulation within 9 weeks (63 days) of missed period by MRM (Menstrual Regulation by Medication), using 200mg of oral Mifepristone followed by buccal Misoprostol 800μg. Study period was from July 2014 to December 2014. Results: Success rates of regimen used in this study that are higher (98%) in case of women <6wks amenorrhoea than that group who have had amenorrhea up to 9 weeks (94%). There were 4 failures (4%), among them 1(2%) from women <6 weeks and 3 (6%) from women >6 weeks who needed surgical evacuation later on. Conclusion: MRM with Mifepristone 200mg followed by buccal Misoprostol 800μg is highly effective and safe. Journal of Armed Forces Medical College Bangladesh Vol.12(1) 2016: 8-11